Jakarta's Indonesian-Chinese Gated Community in Abundance: Tracing the Dutch Colonial Legacy through the Lens of Postcolonial Urbanism - Dhea Ramadhani; Ruben Bima Karia Sianturi (Global South Review, 2026)
As one of Jakarta’s most prominent gated communities, Pantai Indah Kapuk (PIK) is widely recognized for its exclusivity and luxury. However, its spatial configuration is a product of Dutch colonial legacy in Jakarta. Back then, urban planning was deliberately segregated along racial lines through the canal and wall constructions. Among the local ethnic populations in Indonesia, Chinese populations were given the same privileges as Europeans to live inside the walls. Even after the independence of Indonesia, this favoritism fueled socio-political conflicts such as the tragedies of mass violence in 1965 and 1998. In response, affluent communities like PIK emerged as secure enclaves, physically and socially detached from the rest of the city. This research aims to trace the legacy of colonialism in Jakarta on creating the gated communities through a postcolonial urbanism lens. Through a literature review and field research to the PIK gated community in Jakarta by public transportation, this study will observe PIK in terms of the securitization of access and demonstrate that spatial segregation is a product of Dutch colonization.